Project management guide - Ducros, Marc (Editions Technip, 2010)
The purpose of this book is to provide some understanding and guidelines on the way medium sized and large Projects in an international environment can be initiated and managed. Its content is based on the collective experience of the authors obtained during the last forty years with an International Oil & Gas Company, with the rest spent with engineering and construction contractors.
Keywords: Project management -- Handbooks, manuals, etc.; Gas industry -- Management -- Handbooks, manuals, etc.; elektronické knihy; electronic books